The Benefits And Security Of The Interest Of Students At The Muhammadiyah University Of Banjarmasin In The Use Of Mobile Banking: The Benefits And Security Of The Interest Of Students At The Muhammadiyah University Of Banjarmasin In The Use Of Mobile Banking - fai, maulidi; hanifah, hanifah (UMBanjarmasin, 2022)
In Indonesia, mobile banking is not a new thing, because it has become part of banking innovation in following global business competition. Therefore, banking institutions try to provide service satisfaction to their customers by providing banking facilities, in the form ofumobile banking services to conduct transactions or business. This study aims to determine the effect of perceived ease of use, perceived benefits, risks, access capabilities, and security on the use of mobile banking. In this study, researchers used quantitative research. This quantitative choice is because it is a type of research activity whose specifications are systematic, well-planned, and clearly structured from the beginning to the making of research designs, both regarding research objectives, research subjects, research objects, data samples, data sources, and methodologies. Based on the results of the analysis and discussion of the previous discussion, it can be concluded that the security guarantee variable has no partial effect on the benefits of saving customers